Peroxisome Proliferator-Activated Receptor α Attenuates Hypertensive Vascular Remodeling by Protecting Vascular Smooth Muscle Cells from Angiotensin II-Induced ROS Production - Ye Liu; Yan Duan; Nan Zhao; Xinxin Zhu; Xiaoting Yu; Shiyu Jiao; Yanting Song; Li Shi; Yutao Ma; Xia Wang; Baoqi Yu; Aijuan Qu (MDPI AG, 2022)
Vascular remodeling is the fundamental basis for hypertensive disease, in which vascular smooth muscle cell (VSMC) dysfunction plays an essential role. Previous studies suggest that the activation of peroxisome proliferator-activated receptor α (PPARα) by fibrate drugs has cardiovascular benefits independent of the lipid-lowering effects. However, the underlying mechanism remains incompletely understood. This study explored the role of PPARα in angiotensin II (Ang II)-induced vascular remodeling and hypertension using VSMC-specific Ppara-deficient mice. The PPARα expression was markedly downregulated in the VSMCs upon Ang II treatment. A PPARα deficiency in the VSMC significantly aggravated the Ang II-induced hypertension and vascular stiffness, with little influence on the cardiac function. The morphological analyses demonstrated that VSMC-specific Ppara-deficient mice exhibited an aggravated vascular remodeling and oxidative stress. In vitro, a PPARα deficiency dramatically increased the production of mitochondrial reactive oxidative species (ROS) in Ang II-treated primary VSMCs. Finally, the PPARα activation by Wy14643 improved the Ang II-induced ROS production and vascular remodeling in a VSMC PPARα-dependent manner. Taken together, these data suggest that PPARα plays a critical protective role in Ang II-induced hypertension via attenuating ROS production in VSMCs, thus providing a potential therapeutic target for hypertensive diseases.